2003
DOI: 10.1021/es026232a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Non-methane Hydrocarbons Emitted from Various Cookstoves Used in China

Abstract: Emission contributions from cookstoves to indoor, regional, and global air pollution largely depend on stove and fuel types. This paper presents a database on emission factors of speciated non-methane hydrocarbons (NMHCs) for 16 fuel/stove combinations burning 2 types of crop residue, wood, 4 types of coal, kerosene, and 3 types of gaseous fuels. The emission factors are presented both on a fuel mass basis (compound mass per fuel mass) and on a cooking task basis (compound mass per unit energy delivered to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 11 publications
(22 reference statements)
5
63
1
Order By: Relevance
“…5b, although fairly good correlations (r N 0.7, p b 0.001) between toluene and benzene were observed at SY NECP , YC NCP and DH PRD sites, the T/B slopes were quite different. They were 0.20 and 0.40 respectively at SY NECP and YC NCP sites within that of 0.23-0.68 for biomass/biofuel burning (Andreae and Merlet, 2001;Liu et al, 2008;Li et al, 2009;Wang et al, 2009;Akagi et al, 2011) or 0.13-0.71 for coal combustion (Tsai et al, 2003;Liu et al, 2008), implying input from biomass/biofuel burning and coal combustion at the two sites. Contrastingly, the T/B slope of 1.66 at DH PRD site was close to that of~1.6 for vehicle emissions (Perry and Gee, 1995;Gelencser et al, 1997;Wang et al, 2002;Barletta et al, 2005;Tang et al, 2007;Liu et al, 2008;Gentner et al, 2013), indicating the contribution of traffic-related sources.…”
Section: Background Benzene Levelsmentioning
confidence: 69%
See 2 more Smart Citations
“…5b, although fairly good correlations (r N 0.7, p b 0.001) between toluene and benzene were observed at SY NECP , YC NCP and DH PRD sites, the T/B slopes were quite different. They were 0.20 and 0.40 respectively at SY NECP and YC NCP sites within that of 0.23-0.68 for biomass/biofuel burning (Andreae and Merlet, 2001;Liu et al, 2008;Li et al, 2009;Wang et al, 2009;Akagi et al, 2011) or 0.13-0.71 for coal combustion (Tsai et al, 2003;Liu et al, 2008), implying input from biomass/biofuel burning and coal combustion at the two sites. Contrastingly, the T/B slope of 1.66 at DH PRD site was close to that of~1.6 for vehicle emissions (Perry and Gee, 1995;Gelencser et al, 1997;Wang et al, 2002;Barletta et al, 2005;Tang et al, 2007;Liu et al, 2008;Gentner et al, 2013), indicating the contribution of traffic-related sources.…”
Section: Background Benzene Levelsmentioning
confidence: 69%
“…In 2012, 14.6% of the 0.182 billion tons of coal consumed in the Liaoning Province, and 11.4% of the 0.402 billion tons coal consumed in the Shandong Province were used for heating supply (NBSC, 2013b). This increase in coal consumption for domestic heating supply has been assumed to be the major reason for elevated benzene levels in winter, as coal combustion is an important source of benzene (Tsai et al, 2003;Moreira dos Santos et al, 2004;Liu et al, 2008). In fact, a recent study in Beijing revealed that coal combustion contributed significantly more to ambient VOCs in the winter (19%) than in the summer (4%) .…”
Section: Source Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by Wang et al (2009), C6-C7 aromatics, propylene, C2-C3 o-VOC were the major VOC species from typical biomass burning in northern China. Of the hydrocarbons, C2-C3 hydrocarbons and C6-C7 aromatics were abundant both in Liu et al (2008) and Tsai et al (2003) study. Nevertheless, significant variations of the specific proportions of VOC species were identified between this study and previous studies.…”
Section: Source Profilesmentioning
confidence: 86%
“…One reason was the variability of emissions from different burning tests, largely associated with the variations in fire tending behavior (Tsai et al, 2003). The burning cycle usually began with the ignition which was characterized by incomplete combustion, followed by a stable and complete combustion, and ended with combustion of the remaining charcoal.…”
Section: Uncertainty Analysismentioning
confidence: 99%